1973
DOI: 10.1113/jphysiol.1973.sp010141
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activity in isolated bovine mesenteric lymphatics

Abstract: SUMMARY1. Longitudinal tension was measured in isolated segments (approximately 20 mm in length and 2 mm in diameter) of bovine mesenteric lymphatic vessels.2. Seventeen out of thirty-nine vessels showed regular spontaneous rhythmic contractions, the most common frequency being about 2/min. 3. The strength of each contraction was related to the duration of the preceding pause, a longer pause being associated with a stronger contraction.4. Noradrenaline increased the frequency and decreased the amplitude of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 4 publications
1
52
0
Order By: Relevance
“…The activity of the smooth muscle in bovine mesenteric lymphatics differs considerably from that seen in bovine mesenteric veins and arteries (Roddie & Scott, 1969;Mawhinney & Roddie, 1973). Isolated mesenteric veins at 370 C show spontaneous contractions but these are irregular in force and frequency and normally pauses are not seen between contractions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The activity of the smooth muscle in bovine mesenteric lymphatics differs considerably from that seen in bovine mesenteric veins and arteries (Roddie & Scott, 1969;Mawhinney & Roddie, 1973). Isolated mesenteric veins at 370 C show spontaneous contractions but these are irregular in force and frequency and normally pauses are not seen between contractions.…”
Section: Discussionmentioning
confidence: 98%
“…Agents such as increases in local temperature (McHale & Roddie, 1975b) and noradrenaline (Mawhinney & Roddie, 1973) can increase the rate of pace-maker activity in bovine lymphatic muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When tone was reduced, Jl did not change with isoprenaline, decreased with pentobarbitone or with isotonic solutions of MgSO4, mannitol, or glucose as the serosal fluid (Table 2), but appreciably increased with noradrenaline and adrenaline. The increase of Jl by the latter could be related to their effects on the increases in mesenteric lymphatic contractility (Florey, 1927;Ohhashi, Kawai & Azuma, 1978;Mawhinney & Roddie, 1973) which may promote lymph flow. When the luminal fluid was isotonic MgSO4 or LiCl solution, fluid was secreted into the lumen of the intestine and motility was increased to 2-3 +, but Jl was 0 in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…into rat mesentery was followed N. G. McHALE AND I. C. RODDIE by a vigorous contractile spasm of the lacteals near the injection site and a much increased rate of contraction further away. Mawhinney & Roddie (1973) found that noradrenaline had the effect of increasing the frequency of longitudinal contraction of isolated segments of bovine mesenteric lymphatic. Amplitude of contraction decreased as well, but less would have been predicted for a comparable spontaneous rate increase.…”
Section: Introductionmentioning
confidence: 99%